FcRL4+ B-cells in salivary glands of primary Sjögren's syndrome patients. (July 2017) - Haacke, Erlin A.; Bootsma, Hendrika; Spijkervet, Fred K.L.; Visser, Annie; Vissink, Arjan; Kluin, Philip M.; Kroese, Frans G.M.
Abstract: Fc receptor-like protein 4 (FcRL4) is normally expressed on a small subset of mucosa-associated B-cells, as well as on mucosa-associated lymphoid tissue (MALT) lymphoma B-cells. Primary Sjögren's syndrome (pSS) patients have an increased risk of developing MALT lymphomas, preferentially in the parotid glands. For this reason we studied here by immunohistochemistry and mRNA analysis whether FcRL4 expressing B-cells are present in salivary gland tissue (labial and parotid) of pSS patients (n = 54) and non-pSS sicca patients (n = 16) and whether parotid gland MALT lymphomas in pSS patients (n = 49) also express this receptor. We also studied the effect of treatment (rituximab and abatacept) on the presence of FcRL4 + B-cells, and whether numbers in labial gland biopsies at time of diagnosis of pSS can predict whether patients are at risk for MALT lymphoma development. We demonstrate that FcRL4 + cells are present in salivary gland tissue of pSS patients where they are closely associated with ductal epithelial cells forming lymphoepithelial lesions. The glandular FcRL4 + cells are highly proliferative, genuine PAX5 + B-cells. These FcRL4 + B-cells are far more frequent in parotid gland than in labial gland tissue (p = 0.003). We further show that expression of FcRL4 is present in pSS-related parotid MALT lymphomas. The FcRL4 mRNA expression level in parotid MALT lymphoma is increased compared to parotid gland tissue of pSS patients without lymphoma (p = 0.017). However, numbers of FcRL4 + B-cells in labial gland biopsies taken at the time of pSS diagnosis, are not predictive for later development of MALT lymphoma. Reduction of parotid gland FcRL4 + B-cells by rituximab, but not abatacept is accompanied by restoration of the glandular epithelium, illustrating the crosstalk between these B-cells with the ductal cells. In conclusion, intraepithelial FcRL4 + B-cells are present in the salivary glands of pSS patients. These cells are likely involved in the epithelial changes seen in pSS. Their enrichment in parotid glands may explain why MALT lymphomas in pSS patients preferentially develop at this specific location. Highlights: Highly proliferative FcRL4 + B-cells are present in salivary glands of pSS patients. FcRL4 + B-cells are associated with salivary gland ductal epithelium and are enriched in parotid glands. FcRL4 + B-cells can effectively be targeted by rituximab. FcRL4 expression is preserved in pSS associated parotid MALT lymphomas.